Effect of pressure-assisted heat treatment on photoluminescence emission of α-Bi2O3 needles - Schmidt, Samara [UNESP]; Kubaski, Evaldo T.; Volanti, Diogo P. [UNESP]; Sequinel, Thiago; Bezzon, Vinicius Danilo N. [UNESP]; Beltrán, Armando; Tebcherani, Sergio M.; Varela, José A. [UNESP] (Inorganic Chemistry, 2015)
Materials with high photoluminescence (PL) intensity can potentially be used in optical and electronic devices. Although the PL properties of bismuth(III) oxide with a monoclinic crystal structure (α-Bi2O3) have been explored in the past few years, methods of increasing PL emission intensity and information relating PL emission to structural defects are scarce. This research evaluated the effect of a pressure-assisted heat treatment (PAHT) on the PL properties of α-Bi2O3 with a needlelike morphology, which was synthesized via a microwave-assisted hydrothermal (MAH) method. PAHT caused an angular increase between the [BiO6]-[BiO6] clusters of α-Bi2O3, resulting in a significant increase in the PL emission intensity. The Raman and XPS spectra also showed that the α-Bi2O3 PL emissions in the low-energy region (below ∼2.1 eV) are attributed to oxygen vacancies that form defect donor states. The experimental results are in good agreement with first-principles total-energy calculations that were carried out within periodic density functional theory (DFT).